Diseño y aplicación de un módulo de estrategias metodológica para motivar al aprendizaje cooperativo en la enseñanza de ciencias naturales, dirigida a niños y niñas del cuarto año de educación básica de la escuela “Juan Abel Echeverría” sector de colaisa, parroquia san buenaventura cantón Latacunga, provincia de Cotopaxi año lectivo 2012-2013 - SigchaTigasi, Guido Wladimir (2012)
The thesis has as purpose to improve the quality of the education in children´s teaching and learning process fourth year of Basic General Education at "JUAN ABEL ECHEVERRÍA" School located in San Buenaventura Parish, Latacunga Canton, Cotopaxi Province. This work is very significant since it will allow to detect the incidence of the use of motivation strategies in the learning to work in team, with the purpose of improving the yield and the educational quality, for what has intended the following thing Design and Application of a methodological strategies module in order to motivate the cooperative learning in the teaching of natural sciences, the same one that applied in correct way will provide a better learning quality, because according to the demands of the current education teachers should apply new strategies that allow students to build their own knowledge and then they can apply it in the reality of their daily life. The contents outlined offer current and suggested information by experts, professionals in education, allowing this way the effective development of the thematic proposal, the same one that can serve as consultation source to who is interested in the topic.